"Two‐Eyed Seeing": An Indigenous framework to transform fisheries research and management. Issue 2 (19th October 2020) - Reid, Andrea J.; Eckert, Lauren E.; Lane, John‐Francis; Young, Nathan; Hinch, Scott G.; Darimont, Chris T.; Cooke, Steven J.; Ban, Natalie C.; Marshall, Albert
Abstract: Increasingly, fisheries researchers and managers seek or are compelled to "bridge" Indigenous knowledge systems with Western scientific approaches to understanding and governing fisheries. Here, we move beyond the all‐too‐common narrative about integrating or incorporating (too often used as euphemisms for assimilating) other knowledge systems into Western science, instead of building an ethic of knowledge coexistence and complementarity in knowledge generation using Two‐Eyed Seeing as a guiding framework. Two‐Eyed Seeing ( Etuaptmumk in Mi'kmaw) embraces "learning to see from one eye with the strengths of Indigenous knowledges and ways of knowing, and from the other eye with the strengths of mainstream knowledges and ways of knowing, and to use both these eyes together, for the benefit of all, " as envisaged by Elder Dr. Albert Marshall. In this paper, we examine the notion of knowledge dichotomies and imperatives for knowledge coexistence and draw parallels between Two‐Eyed Seeing and other analogous Indigenous frameworks from around the world. It is set apart from other Indigenous frameworks in its explicit action imperative—central to Two‐Eyed Seeing is the notion that knowledge transforms the holder and that the holder bears a responsibility to act on that knowledge. We explore its operationalization through three Canadian aquatic and fisheries case‐studies that co‐develop questions, document and mobilize knowledge, and co‐produce insights and decisions. We argue that Two‐Eyed Seeing provides a pathway to a plural coexistence, where time‐tested Indigenous knowledge systems can be paired with, not subsumed by, Western scientific insights for an equitable and sustainable future.